2016
DOI: 10.1016/j.scitotenv.2016.05.090
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS Imaging evidences spatial differences in the degradation of solid polycaprolactone diol in water under aerobic and denitrifying conditions

Abstract: Degradation of solid polymers in the aquatic environment encompasses a variety of biotic and abiotic processes giving rise to heterogeneous patterns across the surface of the material, which cannot be investigated using conventional Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) that only renders an "average" picture of the sample. In that context, MALDI-TOF MS Imaging (MALDI MSI) provides a rapid and efficient tool to study 2D spatial changes occurred in the chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 27 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…It is also considered to be a powerful tool for synthetic polymers; however, MALDI-MSI in polymer applications is still limited, although the number of reports is increasing. [18][19][20][21][22][23][24][25][26][27] Conventional MALDI-MSI visualizes the spatial distribution of target compounds, which have specified m/z values, by extracting their mass images from the MSI raw data. This method is not suitable for synthetic polymers because they have a mass distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also considered to be a powerful tool for synthetic polymers; however, MALDI-MSI in polymer applications is still limited, although the number of reports is increasing. [18][19][20][21][22][23][24][25][26][27] Conventional MALDI-MSI visualizes the spatial distribution of target compounds, which have specified m/z values, by extracting their mass images from the MSI raw data. This method is not suitable for synthetic polymers because they have a mass distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences in spatial distribution were discussed in previous reports by comparing the mass images of several degrees of polymerization. [21][22][23]26,27 Kune et al suggested drawing the sum of mass images of chemically related compounds using KMD analysis. 28 They have successfully applied the method to find lipids, tetraalkylammoniums, polymers and lipopeptides in complex imaging mass data.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we performed a comparative study on the degradation of a polyester, PCLD, in two aquatic environments, a river and a laboratory mesocosm, applying MALDI-ToF-MS [18]. In a follow-up study [19], we explored the capability of MALDI-MSI as an analytical tool for investigating modifications in the chemical composition at the polymer surface after exposure to either sterile, aerobic, or denitrifying conditions, using PCLD as a probe polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix‐assisted laser desorption/ionization (MALDI) imaging mass spectrometry (IMS) is a powerful technique which allows for both the determination and visualization of the spatial distribution of analytes within a sample . A variety of analytes can be detected, including small molecules, noncovalent complexes, peptides and proteins, lipids, and synthetic polymers . MALDI‐IMS experiments have been performed on a variety of systems, including three‐dimensional cell cultures, animal tissue, whole animal sections, plant tissue, and bacterial biofilms .…”
mentioning
confidence: 99%
“…[2,3] A variety of analytes can be detected, including small molecules, [4,5] noncovalent complexes, [6] peptides and proteins, [7][8][9][10] lipids, [11,12] and synthetic polymers. [13,14] MALDI-IMS experiments have been performed on a variety of systems, including three-dimensional cell cultures, [15] animal tissue, [9,10] whole animal sections, [16,17] plant tissue, [7,18] and bacterial biofilms. [19] A constant push to be able to resolve smaller and smaller spatial features has resulted in the use of smaller laser spots in order to collect MALDI images using the smallest step size possible, with the current state of the art being a 2.5 micron step size.…”
mentioning
confidence: 99%